Tales from the borderlands : making and unmaking the Galician past - Barṭov, ʾOmer (2022)
Focusing on the former province of Galicia, this book tells the story of Europe’s eastern borderlands, stretching from the Baltic to the Balkans, through the eyes of the diverse communities of migrants who settled there for centuries and were murdered or forcibly removed from the borderlands in the course of World War II and its aftermath. Omer Bartov explores the fates and hopes, dreams and disillusionment of the people who lived there, and, through the stories they told about themselves, reconstructs who they were, where they came from, and where they were heading. It was on the borderlands that the expanding great empires—German, Austro-Hungarian, Russian, and Ottoman—overlapped, clashed, and disintegrated. The civilization of these borderlands was a mix of multiple cultures, languages, ethnic groups, religions, and nations that similarly overlapped and clashed. The borderlands became the cradle of modernity. Looking back at it tells us where we came from.